The global meningitis genome partnership. Issue 4 (October 2020) - Rodgers, Elizabeth; Bentley, Stephen D.; Borrow, Ray; Bratcher, Holly B.; Brisse, Sylvain; Brueggemann, Angela B.; Caugant, Dominique A.; Findlow, Jamie; Fox, LeAnne; Glennie, Linda; Harrison, Lee H.; Harrison, Odile B.; et al.
Highlights: Current WGS collections are not representative of the global meningitis picture. A global overview of WGS data is needed for timely public health intervention. WHO roadmap to defeat meningitis is ideal stimulus to improve genomic surveillance. Global Meningitis Genome Partnership will be a major factor in facilitating this. Summary: Genomic surveillance of bacterial meningitis pathogens is essential for effective disease control globally, enabling identification of emerging and expanding strains and consequent public health interventions. While there has been a rise in the use of whole genome sequencing, this has been driven predominately by a subset of countries with adequate capacity and resources. Global capacity to participate in surveillance needs to be expanded, particularly in low and middle-income countries with high disease burdens. In light of this, the WHO-led collaboration, Defeating Meningitis by 2030 Global Roadmap, has called for the establishment of a Global Meningitis Genome Partnership that links resources for: N. meningitidis (Nm), S. pneumoniae (Sp), H. influenzae (Hi) and S. agalactiae (Sa) to improve worldwide co-ordination of strain identification and tracking. Existing platforms containing relevant genomes include: PubMLST: Nm (31, 622), Sp (15, 132), Hi (1935), Sa (9026); The Wellcome Sanger Institute: Nm (13, 711), Sp (> 24, 000), Sa (6200), Hi (1738); and BMGAP: Nm (8785), Hi (2030). A steering group is being established to coordinate the initiative and encourage high-quality data curation. Next steps include: developing guidelines on open-access sharing of genomic data; defining a core set of metadata; and facilitating development of user-friendly interfaces that represent publicly available data.